Validation and Practicality of ESD-Based Ecology and Biodeversity Materials in Enchacing Students’ Digital and Evironmental Literacy - Tri Utami Setianingrum; Bowo Sugiharto; Sarwanto Sarwanto (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to determine the validity and practicality of learning media on ecology and biodiversity, incorporating Education for Sustainable Development (ESD), in improving the digital literacy and environmental literacy skills of lower secondary school students. Methodology: The research method employed was Research and Development (R&D) using Thiagarajan’s development model, which comprises the define, design, develop, and disseminate stages. Experts in media, subject matter, digitalization, and environmental education validated the learning media, whereas 28 Year 7 students and six science teachers at MTsN 2 Karanganyar evaluated its practicality. Main Findings: The study’s results indicate that the learning media received a ‘highly valid’ rating, with validation percentages of 86.75% from media experts, 85.6% from subject matter experts, 82.3% from digitalization experts, and 86.6% from environmental experts. The practicality test yielded 89% ratings from students and 99% ratings from science teachers, both categorized as ‘highly practical’, thus deeming the media suitable for use in junior high school science education. Novelty/Originality of this study: A study on the development of learning media on ecology and biodiversity, designed with learning activities incorporating Education for Sustainable Development. The study addressed gaps in the use of learning media in schools. The implications of this study are that teaching materials on ecology and biodiversity incorporating Education for Sustainable Development (ESD) can be used as a valid and practical alternative learning resource to support science education in lower secondary schools and enhance pupils’ digital and environmental literacy.